2019
DOI: 10.1111/apa.15007
|View full text |Cite
|
Sign up to set email alerts
|

Positive mother‐child interactions and parenting styles were associated with lower screen time in early childhood

Abstract: Aim This study examined long‐term associations between mother‐child interactions and parenting styles and electronic screen time. Methods We studied 280 healthy children (53.2% girls) enrolled at a mean age of 36 ± 0.4 months from February 2015 to September 2016. The study included retrospective data on 267 children who had been recruited from medical facilities in Thailand at 6 months of age. Mother‐child interaction, parenting styles and screen time were assessed at various ages and path analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 28 publications
2
35
0
2
Order By: Relevance
“…Taking into account the multiple negative consequences of excessive ST, interventions aiming at raising parents' awareness about this phenomenon seem imperative. It is necessary for parents to understand that efficient screen use parenting results in less ST [82]. Additionally, it is important for parents to understand that their own screen use behaviors influence those of their children [83].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the multiple negative consequences of excessive ST, interventions aiming at raising parents' awareness about this phenomenon seem imperative. It is necessary for parents to understand that efficient screen use parenting results in less ST [82]. Additionally, it is important for parents to understand that their own screen use behaviors influence those of their children [83].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Mendelsohn et al showed that verbal interactions between mothers and children were limited during screen exposure, with only 42.8% mothers talking to their children while co-viewing educational programs and 21.3% during non-educational programs [63]. Moreover, a prospective study showed that increasing mother-child interaction at 18 months could reduce children's screen time at subsequent two and three years of age [64]. These findings are similar to our results, showing a negative association between screen time and the frequency of caregiver-child interaction.…”
Section: Association Between Early Electronic Screen Exposure and Caregiver-child Interaction Sleep Duration And Outdoor Activitiesmentioning
confidence: 96%
“…Por eso, esta institución recomienda informarles a las familias que las habilidades cognitivas superiores y las funciones ejecutivas imprescindibles para lograr un buen desempeño escolar -tales como la perseverancia en las tareas, el control de los impulsos, la regulación emocional y el pensamiento creativo y flexible-se transmiten mejor mediante el juego no estructurado y social (no digital), así como mediante las interacciones empáticas entre madres/padres e hijas/os. En este sentido, se ha demostrado que la interacción cara a cara es imprescindible para preservar el desarrollo de las competencias sociales y emocionales en las niñas y niños pequeños (Detnakarintra et al, 2019).…”
Section: El Rol Parentalunclassified